Implementing the Merdeka Curriculum in Islamic Religious Education: A Critical Literature Review of Contemporary Challenges and Pedagogical Implications - Cholisha, Dhewy Laily Choirrushsholih; Isnaini, Elisa Nurrahma; Purnomo (Published by the Islamic Religious Education Study Program Faculty of Tarbiyah and Teacher Training Kiai Haji Achmad Siddiq University, Jember, East Java, Indonesia, 2026)
The implementation of Indonesia’s Merdeka Curriculum in Islamic Religious Education has introduced significant pedagogical shifts, yet its enactment in school contexts remains fraught with persistent challenges. This article aims to critically examine contemporary issues surrounding the implementation of the Merdeka Curriculum in IRE, identify their underlying causes, and analyze their pedagogical implications for teaching, learning, and character formation. Employing a critical literature review approach, this study systematically synthesizes recent national and international scholarly works published between 2020 and 2025. The review reveals four interrelated challenges: limited teacher understanding of core curriculum concepts such as learning outcomes (CP), learning pathways (ATP), differentiated instruction, and authentic assessment; inadequate technological infrastructure and instructional resources; insufficient and uneven professional development and mentoring; and structural disparities in school facilities that exacerbate educational inequality. These challenges contribute to uneven student competency attainment, suboptimal learning effectiveness, and constraints on the cultivation of religious and moral character. This article contributes to the discourse on curriculum reform by offering an integrative analytical framework that links curriculum policy, teacher readiness, and pedagogical practice in Islamic Religious Education. It further proposes strategic implications for teacher professional development, school-based support systems, and equitable policy interventions to strengthen the sustainable and just implementation of the Merdeka Curriculum across diverse educational settings.